ENHANCING STUDENTS’ CREATIVITY IN WRITING CONVERSATION FOR MIDWIFERY STUDENTS; A CLASSROOM ACTION RESEARCH - Laora, Kristina (Jurnal Penelitian Pendidikan, 2020)
Writing conversations in English is challenging for most ESL students. Concentration more on other skills, writing seems lagged behind. Indeed, writing is an art done under particular conditions that necessitates more elaboration and clarity compared to other skills. Writing creatively needs to be improved in gaining students’ higher order thinking skill. One of the forms of writing is dialogue. This study focuses on writing medical dialogue for midwifery students. The midwifery students must be creative in writing the dialogue based on the specific topics given. They wrote two kinds of conversation including conversation of arranged admission and conversation of patient suffering from urine infection. The classroom action research was used to find out the students’ difficulties and how do the deal with the difficult topics in medical conversation (dialogues). There are 2 cycles in this case. The treatments are planning, implementing, observation, reflections. The findings showed that the students have difficulties in writing basic dialogue and also they faced difficulties in writing conversations without clues. The process was stopped in the second cycle because the students pass the maximum criteria. In the future, this study will be published in the accredited local journals and it will be useful for the medical students especially midwifery students, lecturers and institutions.